2009 IEEE International Conference on Rehabilitation Robotics 2009
DOI: 10.1109/icorr.2009.5209527
|View full text |Cite
|
Sign up to set email alerts
|

An empirical study with simulated ADL tasks using a vision-guided assistive robot arm

Abstract: In this paper, we describe an empirical study with healthy subjects with simulated ADL tasks using UCF-ARM -a 6-DOF assistive robot that is visually guided through a calibrated stereo camera system fitted in the gripper of Exact Dynamics' Manus ARM. The goal of the research is to reduce time to task completion and cognitive burden for users interacting with an unstructured environment via a Wheelchair Mounted Robotic Arm (WMRA). Our WMRA, UCF-ARM, provides access to a multimodal user-customizable human compute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…As with robotic wheelchairs, for wheelchair-mounted robotic arms there is a question of how to design paradigms for control sharing. Earlier work saw a similar high/low-level control partition, where the user selected the task or goal, which then was executed by the autonomy system (29,138). In some works the human additionally intervened to provide pose corrections (68,78,139) or assist the autonomy (83).…”
Section: Shared Controlmentioning
confidence: 99%
“…As with robotic wheelchairs, for wheelchair-mounted robotic arms there is a question of how to design paradigms for control sharing. Earlier work saw a similar high/low-level control partition, where the user selected the task or goal, which then was executed by the autonomy system (29,138). In some works the human additionally intervened to provide pose corrections (68,78,139) or assist the autonomy (83).…”
Section: Shared Controlmentioning
confidence: 99%
“…The value of speech as an input modality for persons with severe motor impairments to operate assistive machines has been leveraged for use with robotic arms (Busnel et al, 1999; Kim et al, 2009), robotic wheelchairs (Mandel and Frese, 2007) and mobile manipulators (Volosyak et al, 2005). The human typically uses speech to provide high-level goals or teleoperation commands for the autonomy.…”
Section: Related Workmentioning
confidence: 99%
“…These control modalities also have benefits for controlling robotic arms for WMRM systems, though the positioning of the robotic gripper in three-dimensional Cartesian space and prehensile manipulating of objects provide unique challenges. However, existing HCI modalities (Kim et al, 2012) as well as emerging brain computer interfaces (BCI) (Palankar et al, 2009) and state-of-the-art computer vision systems have been shown to be capable controllers for WMRM systems (Kim et al, 2009;Tsui et al, 2007). This latter work has shown that a camera mounted in the hand of the robotic manipulator provides an effective visual interface for WMRM control (Chung and Cooper, 2012;Kim et al, 2012;Tsui et al, 2011).…”
Section: Introductionmentioning
confidence: 99%